In vitro and in vivo analysis of IgG antibody response against 47 kDa immunogenic protein from salivary gland of Aedes albopictus - Oktarianti, Rike; Rizki Amalia, Istiqomah; Firdausi, Shafira; Wathon, Syubbanul; Senjarini, Kartika (Biogenesis: Jurnal Ilmiah Biologi, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus. The virus is transmitted to humans through the blood-feeding activity of Aedes albopictus. This transmission is facilitated by specific proteins of salivary glands mosquito. Based on the previous studies, there are three immunogenic proteins were detected from salivary glands of Ae. albopictus, i.e 31, 47, and 67 kDa. The 47 kDa protein is one of the proteins suspected to be a serpin protein. These proteins are capable of inducing an immune response in the host. This study aims to assess the capacity of the 47 kDa immunogenic protein derived from the salivary glands of Ae. albopictus to elicit host immune responses. This is achieved through IgG analysis conducted both in vitro and in vivo analysis. In vitro IgG antibody response analysis was performed on human serum samples from healthy people, DHF patients and neonates collected from Jember. In vivo IgG antibody response analysis was performed on mice (Mus musculus) that had been injected with 47 kDa protein. IgG level measurement using the ELISA indirect method. According to in vitro examination of IgG antibody response in human samples against 47 kDa salivary protein, the highest IgG levels were detected in healthy samples followed by dengue patients and neonates. This suggests that the 47 kDa protein from Ae. albopictus salivary glands is recognized by human serum and developed into a biomarker for mosquito bites. In vivo examination of the IgG antibody response in mice (M. musculus) injected by 47 kDa protein revealed that the IgG antibody might be increased by repeated exposure to 47 kDa protein. The highest  IgG level was detected in the 6th week after repeated exposure. Repeated exposure of the 47 kDa salivary protein from Ae. albopictus have been demonstrated to elicit a humoral immune response in mice.